2020
DOI: 10.1016/j.biortech.2020.123037
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal in recirculating aquaculture water with high dissolved oxygen conditions using the simultaneous partial nitrification, anammox and denitrification system

Abstract: The efficient removal of nitrogen pollutants in the aquaculture systems is still a challenge due to the low concentration of organic carbon and high concentration of dissolved oxygen (DO) in the wastewater. The simultaneous partial nitrification, anammox and denitrification (SNAD) bioreactor was firstly used for the treatment of aquaculture wastewater in recirculating aquaculture system. The bioreactor operated for 180 days without adding extra organic carbon. After 60-day operation, the bioreactor reached the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Among these, the contributions of Dysgonomonas, Acidobacteria, and Pantoea sp. to the nitrification process have already been reported in previous studies [22][23][24]. Lactobacillus, Erythrobacter, and Mycobacterium are known to be microflora associated with the denitrification process used in wastewater treatment plants [25][26][27].…”
Section: Pcr-dgge Analysis Of the Microflora In The Mbr With Intermitmentioning
confidence: 65%
“…Among these, the contributions of Dysgonomonas, Acidobacteria, and Pantoea sp. to the nitrification process have already been reported in previous studies [22][23][24]. Lactobacillus, Erythrobacter, and Mycobacterium are known to be microflora associated with the denitrification process used in wastewater treatment plants [25][26][27].…”
Section: Pcr-dgge Analysis Of the Microflora In The Mbr With Intermitmentioning
confidence: 65%
“…Through metaproteomic approach, detected the production of denitrifying protein such as nosZ during effective nitrification of ammonia-oxidizing consortia and nitrate was not found to get accumulated in the system thereby ensuring effective denitrification (Kumar et al 2011;Jose et al 2020). Very recently, simultaneous partial nitrification, anammox and denitrification (SNAD) bioreactor was successfully demonstrated for the first time in RAS with high dissolved oxygen conditions and without any additional organic carbon supply (Lu et al 2020). Here, a significant correlation was observed between the nitrogen functional bacteria and their corresponding genes through network analysis.…”
Section: Current Application Status and Prospects Of Nitrification An...mentioning
confidence: 99%
“…The AnAOB activity could be inhibited by the presence of oxygen ( Liu et al, 2016 ); so far, no anammox activity has been reported in pond aquaculture water. However, AnAOB can be detected in aerated systems, such as nitrogen-removing moving bed biofilters ( van Kessel et al, 2010 ; Persson et al, 2014 ), rotating biological contactor and biofilters ( Egli et al, 2003 ), and the simultaneous partial nitrification, anammox, and denitrification (SNAD) bioreactor ( Lu J. et al, 2020 ). They probably inhabit the oxygen-depleted zones of aerated biofilters ( Mulder et al, 1995 ), where an anoxic environment is created by AOA, AOB, and heterotrophic bacteria.…”
Section: Opportunity For Nitrogen Removal By Ammonia-oxidizing Archaea and Anaerobic Ammonia-oxidizing Bacteria In Aquaculture Pondsmentioning
confidence: 99%
“…Research has shown a bioreactor start-up for 180 days without adding extra organic carbon. After a 60-day operation, the bioreactor reached a stable stage with the average concentration of ammonia/nitrate/nitrite/COD in the effluent of 0.26/0.75/0.47/0.27 mg L –1 ( Lu J. et al, 2020 ). Because they do not need extra organic carbon and are energy-saving, SNAD bioreactors have good prospects.…”
Section: Current Application and Prospects Of Ammonia-oxidizing Archaea And Anaerobic Ammonia-oxidizing Bacteria In Pond Aquaculturementioning
confidence: 99%
See 1 more Smart Citation